Hubungan Kerasionalan Peresepan Obat Antihipertensi Dengan Outcome Klinis Pada Pasien Stroke Iskemik Rawat Inap RSUD Dr. Soegiri Lamongan - Muhammad Muhlis; Luthfiyya Iffa Muslimah (Universitas Muhammadiyah Surakarta, 2021)
Ischemic stroke is a disruption of blood supply to the brain caused by the blockage of blood vessels. Hypertension is a comorbid disease in ischemic stroke. Appropriate treatment can affect the success of therapy and the achievement of the desired blood pressure. This study aims to evaluate the rationale for using antihypertensive drugs to achieve clinical outcomes in the form of blood pressure. This study was designed in an observational analytic manner with a cross-sectional approach, retrospective in nature with a purposive sampling method in ischemic stroke patients who received antihypertensive prescriptions in RSUD Dr. Soegiri Lamongan. The sample used was 100 patients. The results showed that the most widely used antihypertensive drugs were CCB with a percentage of 41.8%, ARB with a percentage of 27.6%. The rationale for prescribing was obtained: 100% correct indication, 100% correct patient, 91% correct drug, and 100% correct dose. The results of the Chi-Square test have obtained an expected value of 5, so that it is followed by the Fisher's Test, which obtained a p-value of 0.021 (p 0.05). The conclusion of this study is that patients who received a rational antihypertensive prescription were 91%, for patients who achieved clinical outcomes as much as 86% and there was a relationship between the rationality of prescribing antihypertensive drugs with clinical outcomes in the form of achieving target blood pressure in ischemic stroke patients at RSUD Dr. Soegiri Lamongan.